Depression in people living with HIV and AIDS: A narrative review - Gutiérrez-Velilla, Ester (2025)
Depression has been recognized as one of the most prevalent psychiatric disorders among people living with HIV and AIDS (PLWHA). It is associated with impaired social functioning, decreased quality of life, poor and inadequate adherence to antiretroviral treatment, loss of follow-up, rapid disease progression and increased mortality. Aim: Top carry out a narrative review of the literature to synthesize the main explanatory theories of depresion, its specific characteristics in PLWHA as well as the psychological interventions that have proved effective for its treatment. Method: A systematic search of articles in English and Spanish published between July 2011 and July 2021 in indexed electronic databases (PubMed and Scopus) using the terms HIV, depression, comorbidity, etiology, and psychological. The search complied with the Scale for the Assessment of Narrative Review Articles (SANRA) criteria to ensure the quality of the review and address the research questions. Results: This review highlights the importance of depression in PLWHA and provides health professionals with information to detect and address it. Conclusion: Detection and treatment of depression are essential for improving outcomes in this population. The information synthesized in this review aims to support health professionals in the early detection and psychological treatment of depression in PLWHA.